2023
DOI: 10.3390/rs15143595
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Winter Wheat SPAD Values Based on UAV Multispectral Remote Sensing

Abstract: Unmanned aerial vehicle (UAV) multispectral imagery has been applied in the remote sensing of wheat SPAD (Soil and Plant Analyzer Development) values. However, existing research has yet to consider the influence of different growth stages and UAV flight altitudes on the accuracy of SPAD estimation. This study aims to optimize UAV flight strategies and incorporate multiple feature selection techniques and machine learning algorithms to enhance the accuracy of the SPAD value estimation of different wheat varieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…Therefore, the optimal combination of feature selection methods (recursive feature elimination, Pearson, and correlation-based feature selection) and machine learning regression models (random forest), elastic net, extreme gradient boosting (XGBoost), and backpropagation neural network with machine learning algorithms can predict SPAD values at individual growth stages and across growth stages of the crop from the images obtained by UAV (Yin et al, 2023). In other words, machine learning regression models (random forest), partial least squares (PLS) regression, deep neural network, and extreme gradient boosting (XGBoost) were used to establish SPAD estimation models.…”
Section: Soil Plant Analysis Development Analysis For Paddy Growth Mo...mentioning
confidence: 99%
“…Therefore, the optimal combination of feature selection methods (recursive feature elimination, Pearson, and correlation-based feature selection) and machine learning regression models (random forest), elastic net, extreme gradient boosting (XGBoost), and backpropagation neural network with machine learning algorithms can predict SPAD values at individual growth stages and across growth stages of the crop from the images obtained by UAV (Yin et al, 2023). In other words, machine learning regression models (random forest), partial least squares (PLS) regression, deep neural network, and extreme gradient boosting (XGBoost) were used to establish SPAD estimation models.…”
Section: Soil Plant Analysis Development Analysis For Paddy Growth Mo...mentioning
confidence: 99%
“…For the prediction accuracy of winter wheat bio-parameters values at the four growth stages, LAI: early filling > booting > late jointing > heading, LCC: heading > early filling > booting > late jointing, CCC: booting > early filling > heading > late jointing. The accuracy of bio-parameter estimation varied with different growth stages of winter wheat, which can be attributed to changes in various factors including crop canopy structure, leaf thickness and cell structure, leaf pigment content, and crop coverage [15,31,36,60]. In addition, the LAI, LCC, and CCC change with the increase in leaf size and number in the vertical distribution of wheat, and the growth and senescence of wheat spikes also affect the estimation of wheat canopy reflectance and bio-parameters.…”
Section: Effects Of Crop Phenology On Bio-parameters Estimationmentioning
confidence: 99%
“…Wang [34] and Wang [35] estimated the wheat LCC using multiple ML models combined with the important ranking of the random forest model. Zhu [15] and Yin [36] used multiple MLs combined with filter-based and RFE feature selection to estimate wheat LCC at different growth stages, respectively. These studies indicated that using the ML model alone cannot achieve optimal model accuracy, and the combination of feature selection and ML model can more accurately estimate the LCC of winter wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, LAI estimation based on satellite data falls short in providing refined field-scale monitoring. Unmanned aerial vehicles (UAVs) offer substantial advantages over satellites in terms of enhanced temporal and spatial resolution, alongside greater flexibility ( Li et al., 2019 ; Yin et al., 2023 ). Multispectral cameras are a popular choice among UAV sensors, it can capture spectral information in the red-edge and near-infrared bands, which are crucial for analyzing vegetation ( Yao et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%